A Modulation Driver of Quasi-sinusoidal Asymmetric Current; Instruments and Experimental Techniques; Vol. 44, iss. 2 - Baginskii B. A.; Grebennikov V. V.; Ogorodnikov D. N. Dmitry Nikolaevich; Yaroslavtsev E. V. Evgeniy Vitalievich (2001, 2001)
Title screen